Millennials in the Stacks: Choices, Habits and Attitudes of Frequent Library Users between the Ages of 18–29 in Santiago, Chile. Issue 1 (2nd January 2021) - Cordero, Kristina; Chiuminatto, Pablo; Duncan, Sam; Vera, Eglé
Abstract: Libraries have been rethinking their collections and services in order to remain relevant for new generations. In Chile, adults between 20 and 36 are one-third of the population, yet they are underrepresented in the research on reading preferences and practices. Through a survey of 346 library users, librarian interviews and focus groups, this study sought to learn about library habits and preferences as well as literacy and cultural practices among 18 to 29 year-old library users in Santiago, Chile. Findings reveal a diversity of reading preferences, with an accent on genre fiction and nonfiction; an appreciation of the librarian as mediator and authority, a view of the library as a symbolic and material space; and a migration to the Internet for recommendations, access to books and spaces for new literacy practices. These initial findings underscore the importance of adapting libraries' collections and services as literacy practices evolve among young users in the twenty-first century.